Restructuring and developing lesson plan of CCU course for D3 English students / Yasmin Farani and Maria Dwi Winarni - Farani, Yasmin; Winarni, Maria Dwi (Universiti Teknologi MARA, Kedah, 2024)
Cross Culture Understanding course is a compulsory subject for the fifth semester students of D3 English Program, University of Merdeka Malang. Since one of the researchers was the lecturer of the related subject, she had to use the existing materials, including the lesson plans. In practice, she found out that those lesson plans were not fully work-oriented materials despite her hopes to have the students prepared for working world after they graduate. Based on those facts, the researchers intended to restructure and further develop the existing lesson plans. To do so, the researchers follow Grave’s framework of components of course development process that consists of seven steps. As for restructuring and developing, the role of the researchers is as the primary instrument since this study is a qualitative one. As the secondary instrument, the questionnaire is used to know the students’ opinions about the course in general. In the process of restructuring and developing the lesson plans, the researchers did not use all the Grave’s steps, but particularly focused on the following steps: Need Assessment, Determining Goals and Objectives, and Conceptualizing Content. The result of this study is in the form of a lesson plan for teaching CCU course. In conclusion, the researchers hope that the new lesson plan can be used as a reference for teaching CCU course.